Cross-disciplinary collaboration in research on a specific-purpose language test in the healthcare setting. Issue 1 (29th March 2018) - McNamara, Tim; Elder, Cathie; Flynn, Eleanor; Knoch, Ute; Manias, Elizabth; Woodward-Kron, Robyn; Yahalom, Sharon
Abstract : Central to teaching and assessing languages for specific purposes is collaboration between domain experts and applied linguists; yet, the complexity of the process has been little documented. A project involving collaboration between language testers, applied linguists and healthcare professionals in Australia provided an opportunity for exploration of this complexity. The project focused on interprofessional written communication about patient care, which forms the basis of a writing task in the Occupational English Test (OET), an English for Specific Purposes (ESP) test for health professionals. The project aimed to identify criteria indigenous to the work setting in order to inform the criteria used by language professionals in judging performance on the OET. This methodological paper examines the decisions involved in designing the collaboration and considers the possible effect of decisions on the validity of findings. The decisions include the choice of workplace writing tasks, of participants, of work settings and of written materials to be used as stimuli, the mode of eliciting responses to the stimuli from the domain experts and the coding and interpretation of data. The ways in which the research results are to be implemented in practice are examined, as well as the broader implications for the methodology of ESP research.